At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
split the function into three pieces: (x-3) = 0 (x+8) = 0 (x-11) = 0 solve for x
i dont know how to do that at all...
(x-3) = 0 what is x?
sorry um x = 3? right
yes, now keep going with the other two
(x+8) = 0 x = ?
x= 11 x = -8?
yup, so those are your zeros x = 3, x = 11, x = -8
WOW THANKS A LOT WOOHOO DIDNT KNOW IT WAS THAT EASY CAN U HELP WITH MORE???
sure I guess
What are the factors of 3x2 + 23x − 8? (3x − 4)(x + 2) (3x − 2)(x + 4) (3x − 8)(x + 1) (3x − 1)(x + 8)
do u know???
theres two more if u dont know this one lol :))))
use foil method to expand each one
idk how to do that...
can we come back and u explain later?
i have moere
sure I guess
Factor the GCF: −6m2 + 18m − 36. −6(m2 − 3m + 6) −1(6m2 − 18m + 36) −6m(m2 − 3m + 6) −6(m2 + 3m − 6) can u just give the answer then explain for both im in the middle of a lesson and its about to end lol :))
hint: the greatest common factor is 6, so we divide each term by 6 and write 6 outside
we can also factor out -1, which reverses each of the signs inside the parentheses
so witch one are you on? im leaning towards c
it's not c you can't factor out m since not every term has m in it (36 doesn't have m)
like I said before... the GCF is -6 which goes on the outside of the parentheses... then we reverse the signs
ok so witch one???
i divided all of em
multiply each of the answer choices out to see which one matches the original hint: (A-B)(C+D) = A*C + A*D - B*C - B*D
so, using our first answer choice as an example... (A-B)(C+D) = A*C + A*D - B*C - B*D (3x − 4)(x + 2) = (3x)(x) + 2(3x) - 4*x - 8 = 3x^2 + 2x - 8 which does NOT match the original so we keep going
ok so its not a.. how do u find like the a*c and etc..?
you match up the numbers....
compare: (A-B)(C+D) = (3x − 4)(x + 2)
A = 3x, B = 4, C = x, and so on...
ahhh ok ill try one second thanks
I'm not sure where you're getting those numbers...
(3x-2)(x+4) = (A-B)(C+D)
first tell me what A, B, C, and D are
a= 3 b = -2 c = x d = 4?
am i right
check A and B again
I dont have any time can u just tell me and explain because im getting really confused
please please please
THANK YOU SO MUCH OMG YOU'RE A LIFE SAVER HOLY CRAP
C = x, D = 4
now use our formula...
(A-B)(C+D) = A*C + A*D - B*C - B*D
OH OK 4x + 12 and -2x - 8???
is that right?
i got it wrong didnt i :C